N‐acetylcysteine as a new prominent approach for treating psychiatric disorders. (5th May 2021) - Smaga, Irena; Frankowska, Małgorzata; Filip, Małgorzata
Abstract : N ‐acetylcysteine (NAC) is a well‐known and safe mucolytic agent, also used in patients with paracetamol overdose. In addition to these effects, recent preclinical and clinical studies have shown that NAC exerts beneficial effects on different psychiatric disorders. Many potential mechanisms have been proposed to underlie the therapeutic effects of NAC, including the regulation of several neurotransmitters, oxidative homeostasis, and inflammatory mediators. In this paper, we summarize the current knowledge on the ability of NAC to ameliorate symptoms and neuropathologies related to different psychiatric disorders, including attention deficit hyperactivity disorder, anxiety, bipolar disorder, depression, obsessive–compulsive disorder, obsessive–compulsive‐related disorder, posttraumatic stress disorder, and schizophrenia. Although preclinical studies have shown a positive effect of NAC on animal models of psychiatric disorders, the clinical efficacy of NAC is not fully established. NAC remains a strong candidate for adjunct treatment for many psychiatric disorders, but additional preclinical and clinical studies are needed. Abstract : ​